Evaluation of exhaust emissions of agricultural tractors using portable emissions measurement system in Korean paddy field - Wan-Soo Kim; Seung-Min Baek; Seung-Yun Baek; Hyeon-Ho Jeon; Md. Abu Ayub Siddique; Taek-Jin Kim; Ryu-Gap Lim; Yong-Joo Kim (Scientific Reports, 2024)
Abstract Recently, diesel engine emissions have been designated as a first-class carcinogen by the World Health Organization (WHO). As such, problems with diesel engine emissions continue to increase around the world. This study aimed to analyze the emissions (CO, NOx, PM) of agricultural tractors during farming operations in order to build a reliable national inventory of air pollutant emissions. Emission data were collected using a portable emission measurement system during actual agricultural operation. The load factor (LF) of the engine was calculated using the collected engine information, the emission factor was analyzed using the LF and the measured emission. The LF was significantly different from the current standard value of 0.48, which is used in Korea to calculate exhaust emissions. The deviation ratio of the emission factor was 0.039 ~ 56.59 compared to Tier-4 emission regulation standards. Under many conditions, the calculated emission factor was higher than the emission limit. Thus, this study provides useful information for emission inventory construction through emission calculation under actual conditions and suggests the need to realize the currently applied emission factor.